Dominant mutations in the cation channel gene transient receptor potential vanilloid 4 cause an unusual spectrum of neuropathies. - Zimoń, M; Baets, J; Auer-Grumbach, M; Berciano, J; Garcia, A; Lopez-Laso, E; Merlini, L; Hilton-Jones, D; McEntagart, M; Crosby, A; Barisic, N; Boltshauser, E; et al. (2010)
Hereditary neuropathies form a heterogeneous group of disorders for which over 40 causal genes have been identified to date. Recently, dominant mutations in the transient receptor potential vanilloid 4 gene were found to be associated with three distinct neuromuscular phenotypes: hereditary motor and sensory neuropathy 2C, scapuloperoneal spinal muscular atrophy and congenital distal spinal muscular atrophy. Transient receptor potential vanilloid 4 encodes a cation channel previously implicated in several types of dominantly inherited bone dysplasia syndromes. We performed DNA sequencing of the coding regions of transient receptor potential vanilloid 4 in a cohort of 145 patients with various types of hereditary neuropathy and identified five different heterozygous missense mutations in eight unrelated families. One mutation arose de novo in an isolated patient, and the remainder segregated in families. Two of the mutations were recurrent in unrelated families. Four mutations in transient receptor potential vanilloid 4 targeted conserved arginine residues in the ankyrin repeat domain, which is believed to be important in protein-protein interactions. Striking phenotypic variability between and within families was observed. The majority of patients displayed a predominantly, or pure, motor neuropathy with axonal characteristics observed on electrophysiological testing. The age of onset varied widely, ranging from congenital to late adulthood onset. Various combinations of additional features were present in most patients including vocal fold paralysis, scapular weakness, contractures and hearing loss. We identified six asymptomatic mutation carriers, indicating reduced penetrance of the transient receptor potential vanilloid 4 defects. This finding is relatively unusual in the context of hereditary neuropathies and has important implications for diagnostic testing and genetic counselling.